PENGARUH MOTIVASI, DISIPLIN KERJA DAN PELATIHAN TERHADAP KINERJA KARAWAN BAGIAN BENGKEL PADA PT. NASMOCO PEMUDA SEMARANG - Windi Mahastuti; Saryadi Saryadi; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2014)
Human resource management plays an active role in improving employee performance through a number of variables that influence it, including motivation, work discipline, training and employee performance. PT. Nasmoco Pemuda Semarang is a private company which is engaged in the sale and repair of Toyota brand cars. But there are still some problem regarding employee performance workshop in PT. Nasmoco Pemuda Semarang who do not reach the standard. So that this research can provide insight about the constraints experienced by employees of the workshop PT. Nasmoco Pemuda Semarang.. This performance type of risearch is used an explanatory research approach to the 42 respondents with sampling techniques saturated. Data collection techniques in this study use interviews, questionnaires and literature study. The data obtained were analyzed quantitatively by using tools such as cross-table analysis, test validity, reliability testing, simple linear regression, multiple linear regression and hypothesis testing with the t test and F test. Results of statistical analysis known simple linear regression equation between motivation and performance of employees is Y = 13.710 + 0.274 X1, then the discipline of working with employee performance equation is Y = 12.280 + 0.563 X2. While the training with employee performance is Y = 17.258 + 0.438 X3. Together - equal influence motivation, work discipline and training on employee performance can be determined by using linear analysis. The result of the calculation is Y = 9.651 + 0.171 X1 + 0.190 X2 + 0.172 X3.The conclusion of this study is that there is a positive correlation between motivation, disilpin work and training on employee performance workshop part of PT. Nasmoco Pemuda Semarang. Recommendations for improving employee performance in order to improve the company's attention to motivation, work discipline and training that will ultimately improve the performance of employees.